Cuckoo parasitism, egg mimicry and egg rejection in two sympatric hosts - Guo Zhong (15424978) (2025)
This study was conducted from March to August 2018–2022 in the Liuzhi region of Guizhou, southwestern China (26°13′ N, 106°42′ E). The study area is mainly a karst landscape type with a mosaic of villages, cultivated land, scrub forest, and barren slopes. The retention of traditional agricultural practices might play an important role in the distribution and breeding of birds in the area (Zhong et al., 2023). In the present study, we compared the cuckoo parasitism rates and egg mimicry levels of two sympatric hosts of the common cuckoo (Cuculus canorus), the stonechat (Saxicola torquatus) and the grey bushchat (Saxicola ferrea), and tested the recognition of model and true eggs, with different levels of mimicry, by both hosts in field experiments. The results showed that cuckoo parasitism rate of the grey bushchat was higher and the degree of egg mimicry was better than those of the stonechat. Egg experiments showed that egg background color is an important recognition cue for both hosts, and the grey bushchat also showed higher levels of egg recognition and egg rejection. Our study supports the evolutionary lag hypothesis, implying that arms race of the grey bushchat with the common cuckoo is at a higher degree at the egg stage compared to that with the stonechat. However, further in-depth comparative studies are required to understand whether similar trends of coevolution occur at other breeding stages, such as nest defense and nestling recognition.